BARRIERS TO SEXUAL PLEASURE: SEXUAL CHARACTERISTIC DIFFERENCES THROUGHOUT THE DEVELOPMENTAL STAGES OF ADULTHOOD. (11th November 2018) - Reinhardt, R; Moore, Z; Bennett, R; Lapham, A; Stripling, A
Abstract: Throughout the developmental stages of adulthood changes in sexual functioning have been noted. Despite knowledge of these changes, exploration of specific barriers remain under-examined. Understanding group differences in sexual characteristics will yield increased knowledge for healthcare providers, and enhance barrier-specific treatment. To better understand sexual characteristics 1, 477 primarily male (51.9%) participants aged 42 to 93 were selected from the de-identified MIDUS-3 database. A one-way ANOVA was utilized to examine self-reported sexual characteristics by age (i.e. young middle-aged adults 42–54 (n=515), older middle-aged adults 55–64 (n=458), and older adults aged 65 and over (n=504)). Significant main effects were found for age and rate of control over sexual aspect of life F(2, 1468)= 7.260 p<.001, importance of sexual expression in relationships F(2, 1474)=4.527 p=.011, and Pain/Discomfort in sexual interactions F(2, 1467)= 4.721 p<.009. Bonferroni-corrected pairwise comparisons revealed that Group 1 reported more importance than Group 2 (p<.008) and higher rate of control compared to Group 2 (p<.003) and Group 3 (p<.003). Results further indicated that Group 2 experiences more sexual pain/discomfort than Group 3 (p<.006). Challenges and barriers regarding ones sexual health influences an individual's well-being, specifically the recognition and promotion of sexual pleasure (Hull, 2006). The implications of this study assist in identifying and disseminating the barriers associated with sexual pleasure. The results suggest that older middle-aged adults reported more pain/discomfort during sexual interactions than older adults. Future research should focus on identifying physiological/biological changes or environmental factors that may be influencing these barriers, and therefore influencing quality of life and well-being.